The Extracellular Matrix and Biocompatible Materials in Glioblastoma Treatment - Belousov, Andrei; Titov, Sergei; Shved, Nikita; Garbuz, Mikhail; Malykin, Grigorii; Gulaia, Valeriia; Kagansky, Alexander; Kumeiko, Vadim (Frontiers in Bioengineering and Biotechnology, 2019)
During cancer genesis, the extracellular matrix (ECM) in the human brain undergoes important transformations, starting to resemble embryonic brain cell milieu with a much denser structure. However, the stiffness of the tumor ECM does not preclude cancer cells from migration. The importance of the ECM role in normal brain tissue as well as in tumor homeostasis has engaged much effort in trials to implement ECM as a target and an instrument in the treatment of brain cancers. This review provides a detailed analysis of both experimental and applied approaches in combined therapy for gliomas in adults. In general, matrix materials for glioma treatment should have properties facilitating the simplest delivery into the body. Hence, to deliver an artificial implant directly into the operation cavity it should be packed into a gel form, while for bloodstream injections matrix needs to be in the form of polymer micelles, nanoparticles, etc. Furthermore, the delivered material should mimic biomechanical properties of the native tissue, support vital functions, and slow down or stop the proliferation of surrounding cells for a prolonged period. The authors propose a two-step approach aimed, on the one hand, at elimination of remaining cancer cells and on the other hand, at restoring normal brain tissue. Thereby, the first bioartificial matrix to be applied should have relatively low elastic modulus should be loaded with anticancer drugs, while the second material with a higher elastic modulus for neurite outgrowth support should contain specific factors stimulating neuroregeneration.